Response of Carrot (Daucus carota L.) to Supplementary Irrigation under Rain-Fed Agriculture at Jimma and Gera, Jimma Zone, South West Ethiopia - Etefa Tilahun Ashine; Minda Tadesse Bedane; Adissu Asefa Mengesha (Advances in Agriculture)
Evaluating supplementary irrigation under rain-fed agriculture could help to determine the amount of water depth for water management and increasing productivity. Thus, this study was conducted at the Jimma and Gera to determine the effect of supplementary irrigation (SI) on carrot production. Eight treatments with three replications on a field plot of 9 m2 were used for conducting the experiment. Crop water requirement (ETc) was calculated from reference evapotranspiration (ETo) and crop coefficient (Kc) using CropWat 8.0 software. Yield and yield component data were collected from the field and analyzed using the statistical analysis system (SAS) software 9.0. The result revealed that root shoulder diameter, fresh biomass, and fresh root weight had significant (p <0.05) effects between the treatments, but there was no significant difference (p >0.05) between treatments on plant height and carrot root length at both locations. The highest and lowest plant heights were recorded at 75% SI and at a rain-fed treatment. A root shoulder diameters of 38.37 and 37.86 mm were recorded at Jimma and Gera, respectively, from the application of 75% and two SI at flowering and fruit setting treatment. The application of 75% SI gave the highest root length. A maximum fresh biomass of 3,038.6 kg/ha was obtained at 75% SI, and a minimum fresh biomass of 1,640.00 kg/ha was recorded from the rain-fed treatment at JARC. Application of 75% SI gave the maximum fresh biomass (2,388.9 kg/ha) at Gera, and a minimum fresh biomass of 1,277.8 kg/ha was recorded from rain fed. An application of 75% SI gave the highest fresh root weight of 7,430.6 kg/ha at JARC. In the study, the application of 75% SI gave the highest (6,388.9 kg/ha) fresh root weight, and the lowest was recorded at rain fed (3,883.3 kg/ha). Therefore, for optimum production, 75% SI was recommended for the production of carrots. The total net benefit from the production of carrots was in the range of 36,659–46,950 ETB per hectare at Jimma and from 24,828 up to 39,399 ETB per hectar at Gera. The maximum and minimum marginal return rate (MRR) at Jimma were 300.97%, which is at 75% SI and 43.69%, which is at 25% supplementary irrigation, respectively. At Gera, the maximum and minimum MRR were 490.95%, which were at 25% supplementary irrigation, and the minimum was 23.18%, which was at full supplementary irrigation. Therefore, to get an economic benefit, supplementing carrot crop at 75% irrigation was recommended for both Gera and JARC.